Influence of the dissipative contact models on the dynamic response of multibody systems - Moreira, Pedro (2011)
The constitutive law used to describe the contact-impact events plays a crucial role in engineering applications. This paper studies the influence of different contact force models on the simulation of the dynamic response of multibody systems. The main issues associated with the most common continuous elastic and dissipative contact force models are presented and discussed. The contact force models are used for the simulation of a bouncing ball problem. The dynamic analysis of different multibody systems shows that the prediction of the dynamic behavior of hard and soft contacting surfaces depends on the selection of the contact force model.